Intestinal Immune Dysregulation Driven by Dysbiosis Promotes Barrier Disruption and Bacterial Translocation in Rats With Cirrhosis. Issue 3 (5th March 2019) - Muñoz, Leticia; Borrero, María‐José; Úbeda, María; Conde, Elisa; del Campo, Rosa; Rodríguez‐Serrano, Macarena; Lario, Margaret; Sánchez‐Díaz, Ana‐María; Pastor, Oscar; Díaz, David; García‐Bermejo, Laura; Monserrat, Jorge; et al.
Abstract : In cirrhosis, intestinal dysbiosis, intestinal barrier impairment, and systemic immune system abnormalities lead to gut bacterial translocation (GBT) and bacterial infection. However, intestinal immune system dysfunction and its contribution to barrier damage are poorly understood. This study correlates immune system dysregulation in the intestines of rats at different stages of CCl4 ‐induced cirrhosis with barrier function and pathogenic microbiota. The following variables were addressed in the small intestine: intraepithelial lymphocyte (IEL) and lamina propria lymphocyte (LPL) activation status and cytokine production (flow cytometry), cytokine mRNA and protein expression (quantitative real‐time PCR and immunofluorescence), microbiota composition of ileum content (16S recombinant DNA massive sequencing), permeability (fecal albumin loss), and epithelial junctions (immunohistochemistry and immunofluorescence). The intestinal mucosa in rats with cirrhosis showed a proinflammatory pattern of immune dysregulation in IELs and LPLs, which featured the expansion of activated lymphocytes, switch to a T helper 1 (Th1) regulatory pattern, and Th17 reduction. In rats with cirrhosis with ascites, this state was associated with epithelial junction protein disruption, fecal albumin loss, and GBT. Direct correlations ( P < 0.01) were observed between elevated interferon gamma (IFNγ)‐expressing T cytotoxic LPLs and fecal albumin and between inflammatory taxa abundance and IFNγ‐producing immune cells in the ileum. Bowel decontamination led to redistributed microbiota composition, reduced proinflammatory activation of mucosal immune cells, normalized fecal albumin levels, and diminished GBT; but there were no modifications in Th17 depletion. Conclusion : The intestinal mucosa of rats with cirrhosis acquires a proinflammatory profile of immune dysregulation that parallels the severity of cirrhosis; this impaired intestinal immune response is driven by gut dysbiosis and leads to disrupted barrier function, promoting GBT.